The Innocent Man : Murder and Injustice in a Small Town - Grisham, John; Copyright Paperback Collection (Library of Congress) (New York : Bantam Dell, 2007)
read by Craig Wasson
Keywords: Williamson, Ronald Keith, -- 1953-2004 -- Trials, litigation, etc; Trials (Murder) -- Oklahoma; Judicial error -- Oklahoma; Capital punishment -- Oklahoma